DEVELOPMENT OF BIPA READING ASSESSMENT FOR BASIC LEVEL IN ESSA BAUCAU SCHOOL, TIMOR LESTE - RIBEIRO, GIL TOME; Idris, Nuny S.; Widia, Ida (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. This study addresses challenges in reading assessment for basic-level Indonesian Language Learning for Foreign Speakers (BIPA). Research Purpose. Creating an instrument that is valid, reliable, practical, and adapted to learners’ language backgrounds. Research Method. Using the ADDIE Research and Development model, the study involved 45 students selected purposively. Data were collected through expert validation, student questionnaires, and reading tests. Validation was done by three experts, with trials conducted in two stages: a limited trial with 15 students and a broader trial with 45 students. Validity was assessed using Content Validity Ratio and Index, reliability with Cronbach’s Alpha, practicality by positive response rates, and effectiveness by comparing pre- and post-test results. Findings. The developed instrument showed high validity, with 93.3% of items rated highly valid by experts and an average score of 4.17 on a 5-point scale. Reliability was strong, indicated by a Cronbach’s Alpha of 0.87. Practicality measured through positive feedback was 83.5% from students and 90.5% from teachers. Effectiveness was demonstrated by an increase in average student reading scores from 65.2 to 78.4 and a 23% rise in learning motivation. The instrument covers literal, inferential, and critical comprehension, matching learners’ characteristics well. Conclusion. This study provides a well-rounded reading assessment tool that can significantly improve reading skills measurement in BIPA learning contexts.